The impact of Currency Depreciation in Developing Countries - Agyemang, Nana Kwadwo (International Journal of Psychosocial Rehabilitation, 2020)
This paper is aimed at examining the economic effects of cpurrency depreciation in developing countries.The study will also focus on the Marshal-learner model which is an extension of the Marshal’s model in examining whether a depreciation in the exchange rate is likely to cause a balance of trade (Carbaugh 435) especially in developing countries where it is common that the balance of trade is likely to deteriorate due to currency depreciation. The Marshal’s model states that devaluation or depreciation of currency makes export relatively cheaper and import relatively expensive. Also, an increase in the demand for foreign goods in the home country increases the demand for foreign currency which causes depreciation as well as trade deficits adversely affecting developing economies. The study also analyses the reasons government resort to currency devaluation and its effects on the imports and exports in the home country.